Influence of three accuracy levels of knowledge of results on motor skill acquisition - Sanchez, F. J. N.; Gonzalez, J. G. (Journal of Human Sport & Exercise, 2010)
This study analyse the influence of Knowledge of Results (KR) with different accuracy levels on the learning rate of a throwing skill of spatial non-vision accuracy, during the acquisition stage. We assessed the number of successful events, the distance from the target and the consistency of the responses obtained by 180 subjects. We applied three accuracy levels: KR1 - subjects were informed about reaching the target or not; KR2 - informed about the direction of the failure events; and KR3 - informed about the direction and quantification of the failure events. All groups improved their rate of success -15.56% in KR1, 14.45% in KR3 (p < 0.001) and 14.16% in KR2 (p=0.001)- as well as their consistency level after the acquisition stage. After 15 minutes without KR, we found main differences related to the rate of success in the retention stage between KR2 and KR1 (p=0.026), and between KR3 and KR1 (p=0.001), but not between KR2 and KR3. We can conclude that, a less precise KR, aimed just to the direction of the failure events, resulted more efficient at an initial learning stage than a more precise KR, aimed to the direction and the distance of the failure events.